Increasing plasma ketamine concentrations decrease the minimum alveolar concentration of isoflurane in rabbits - Barter, Linda S.; Pypendop, Bruno H. (Frontiers in Veterinary Science, 2025)
To evaluate the effects of increasing plasma ketamine concentration on isoflurane minimum alveolar concentration (MAC) in rabbits, six New Zealand white rabbits weighing 4.21 ± 0.35 kg were anesthetized with isoflurane in oxygen. Ketamine was given intravenously to target pseudo-steady-state plasma concentrations of 0.5, 1, 2, 4, 8, and 12 μg mL−1. MAC, heart rate, arterial blood pressure, body temperature, end-tidal carbon dioxide concentration, and plasma ketamine concentration were measured at each targeted ketamine concentration. A pharmacodynamic model was fitted to the plasma ketamine concentration-MAC data. The measured plasma ketamine concentrations were 0.53 ± 0.14, 1.25 ± 0.2, 2.64 ± 0.44, 5.11 ± 1.18, 8.96 ± 2.03, and 18.07 ± 4.2 μg mL−1, and isoflurane MAC values (% atm) were 1.66 ± 0.04, 1.39 ± 0.17, 1.16 ± 0.13, 1.02 ± 0.15, 0.86 ± 0.17, and 0.71 ± 0.06 for the six targeted plasma ketamine concentrations. MAC was significantly lower than baseline for the target concentration of 1 μg mL−1 and above. Heart rate was significantly reduced from baseline at plasma target ketamine concentrations of 2 μg mL−1 and higher. At target ketamine concentrations of 8 and 12 mcg mL−1, increased muscle tone and spontaneous movement were observed in some rabbits, requiring active cooling to maintain normothermia. Recoveries were unremarkable. MAC at plasma ketamine concentration C was predicted to be 1.85−1.25×C2.96+C. Increasing ketamine concentrations reduced isoflurane MAC in healthy female New Zealand White rabbits. Plasma ketamine concentrations between 1 and 4 μg mL−1 may elicit benefit with minimal adverse effects.